Indigenous beliefs and customs, the South African criminal law, and human rights: identifying the issues*. Issue 3 (2nd September 2021) - Matthee, Jacques
ABSTRACT: African Customary law and the South African common law enjoy equal recognition in the South African legal system. However, their equal status results in various conflict situations between them, especially in the South African criminal law. This paper shows that the indigenous belief in witchcraft (including witch-killings), the indigenous belief in the tokoloshe and the use of muti -medicine (including muti -murders), as well as the indigenous custom of ukuthwala, can result in the commission of common law and statutory crimes in South Africa. These are then known as "culturally motivated" crimes. In addition, this paper shows that the indigenous beliefs and custom above can also violate fundamental human rights entrenched in the South African Constitution. In this regard, this paper also outlines the consequences that an accused can face for infringing upon a victim's fundamental human rights through the commission of a culturally motivated crime.